Preparation and application of a Pd nanoparticle modified hydrogen production photocatalytic material
By loading Ce2S3 on the surface of UiO-66-NH2 material and introducing oxygen vacancy defects, and then introducing Pd nanoparticles on its surface, a Pd nanoparticle-modified Ce2S3/UiO-66-NH2 composite material was prepared, which solved the problem of existing photocatalytic hydrogen production. Due to the low light absorption capacity of the material and the easy recombination of photogenerated charges, efficient photocatalytic hydrogen production has been achieved.
Patent Information
- Application Number
- CN202411719924.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-28
AI Technical Summary
Existing photocatalytic hydrogen production materials face the problems of low light absorption capacity and easy recombination of photogenerated charges, which makes the technology unable to achieve industrial application promotion.
By loading CE2S3 on the surface of the UIO-66-NH2 material and introducing oxygen vacancy defects, the light sedimentation method is used to induce the PD nanoparticles to anchor on the surface of the material to prepare the PD nanoparticles to modify the CE2S3/UIO-66-NH2 composite material.
The photocatalytic hydrogenation efficiency of this composite material has been significantly improved, and the hydrogen production activity reaches 217.62 μmol/h/g, which has a good optical catalytic hydrogen application prospect.
Smart Images

Figure CN119215987B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalysts, and specifically relates to the preparation and application of a Pd nanoparticle-modified hydrogen-producing photocatalytic material. Background Art
[0002] Photocatalytic hydrogen production is a new energy production technology that uses light energy to catalytically convert water into hydrogen. It has the advantages of low equipment investment, green environmental protection, and flexible application. However, the photocatalytic hydrogen production process is still in the early stages of research and development. Most photocatalytic materials face problems such as low light absorption capacity and easy recombination of photogenerated charges, which makes it impossible to achieve industrial application and promotion of photocatalytic hydrogen production technology. Therefore, the research and development of efficient photocatalysts is of great significance to the large-scale promotion and utilization of photocatalytic hydrogen production technology. Summary of the invention
[0003] To this end, the present invention proposes a preparation and application of a Pd nanoparticle-modified hydrogen production photocatalytic material to solve the above-mentioned technical problems, including:
[0004] The preparation method of Pd nanoparticle modified hydrogen production photocatalytic material is as follows:
[0005] S1: Grind thioacetamide into powder, dissolve in water, stir and dissolve, add Ce(NO3)3 solution to thioacetamide solution, add UiO-66-NH2 material, dry and hydrothermally react to obtain Ce2S3 / UiO-66-NH2 material;
[0006] S2: Ce2S3 / UiO-66-NH2 material and NaBH4 were mixed and ground, heated at 300-400°C under vacuum conditions for 0.5-1.5 h, cooled, washed and dried to obtain Ce2S3 / UiO-66-NH2 material containing oxygen vacancies;
[0007] S3: Ce2S3 / UiO-66-NH2 material containing oxygen vacancies was added into distilled water to dissolve, methanol solution and PdCl2 HCl solution were added, mixed evenly, irradiated with 300 W xenon lamp light source for 30 min, centrifuged, washed and dried to obtain Pd nanoparticle modified Ce2S3 / UiO-66-NH2 composite material;
[0008] Among them, the ratio of thioacetamide, water and UiO-66-NH2 material is 5g:50mL:0.052-0.835g, the mass ratio of Ce2S3 / UiO-66-NH2 material and NaBH4 is 2:1, and the added amounts of Ce2S3 / UiO-66-NH2 material containing oxygen vacancies, distilled water and HCl solution containing PdCl2 are: 0.4g:160mL:77mL.
[0009] Preferably, the amount of cerium nitrate solution added is such that the molar ratio of Ce:S elements in the solution is 2:3.
[0010] Preferably, the preparation method of the UiO-66-NH2 material is:
[0011] (1) After 2-aminoterephthalic acid is dissolved in N,N-dimethylformamide, zirconium tetrachloride and acetic acid solution are added and fully dissolved;
[0012] (2) After heating at 100-140°C for 8-16 hours, the mixture is cooled, centrifuged, washed and dried to obtain UiO-66-NH2 powder.
[0013] Preferably, the added amounts of 2-aminoterephthalic acid, N,N-dimethylformamide, zirconium tetrachloride and acetic acid solution are 0.405 g: 20 mL: 0.525 g: 8.5 mL.
[0014] Preferably, the preparation method of the HCl solution containing PdCl2 is: take a 36% HCl solution, dilute it into distilled water, add PdCl2 powder to the diluted HCl solution to obtain a PdCl2 HCl solution, and the added amounts of the 36% HCl solution, distilled water and PdCl2 are 7mL:70mL:0.01mol.
[0015] Preferably, the mass ratio of the Ce2S3 / UiO-66-NH2 material and NaBH4 is 2:1.
[0016] Preferably, the added amounts of the Ce2S3 / UiO-66-NH2 material containing oxygen vacancies, distilled water and the HCl solution containing PdCl2 are: 0.4 g: 160 mL: 77 mL.
[0017] The present invention further protects the application of Pd nanoparticle modified hydrogen production photocatalytic materials in photocatalytic hydrogen production technology.
[0018] The beneficial effects of the present invention are:
[0019] (1) The MOFs material UiO-66-NH2 with ultra-large specific surface area and highly ordered pore structure was prepared by a hydrothermal method. The semiconductor material Ce2S3 was then loaded on the surface of UiO-66-NH2 by a precipitation method. Oxygen vacancy defects were introduced on the surface of the Ce2S3 / UiO-66-NH2 heterostructure by a chemical reduction method as photogenerated electron capture centers. Pd nanoparticles were induced and anchored on the material surface by a photodeposition method. Finally, a new Pd nanoparticle-modified Ce2S3 / UiO-66-NH2 composite material was prepared for photocatalytic hydrogen production.
[0020] (2) The introduction of oxygen vacancies in Pd nanoparticle-modified Ce2S3 / UiO-66-NH2 composites can effectively reduce the agglomeration of Pd nanoparticles. The uniformly dispersed Pd nanoparticles have a surface plasmon resonance effect, which can effectively improve the light absorption capacity. The built-in electric field formed in the Ce2S3 / UiO-66-NH2 heterostructure can drive the directional movement of photogenerated charges and reduce the recombination rate of photogenerated charges. The synergistic effect of the two can enhance the photocatalytic hydrogen production efficiency of Pd nanoparticle-modified Ce2S3 / UiO-66-NH2 composites.
[0021] (3) Experimental results show that compared with pure UiO-66-NH2 and Ce2S3, the photocatalytic efficiency of Pd nanoparticle-modified Ce2S3 / UiO-66-NH2 composite materials is significantly improved, and the maximum hydrogen production activity can reach 217.62 μmol / h / g, which has good application prospects in photocatalytic hydrogen production. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 UV-visible absorption spectrum of catalytic materials.
[0023] Figure 2 To test the activity of catalyst for hydrogen production.
[0024] Figure 3 SEM image of UiO-66-NH2.
[0025] Figure 4 SEM image of Ce2S3.
[0026] Figure 5 SEM image of Ce2S3 / UiO-66-NH2 modified with Pd nanoparticles.
[0027] Figure 6 Elemental analysis diagram of Ce2S3 / UiO-66-NH2 modified with Pd nanoparticles.
[0028] Figure 7 TEM image of Ce2S3 / UiO-66-NH2 modified with Pd nanoparticles. DETAILED DESCRIPTION
[0029] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1
[0031] This embodiment provides the preparation of a Pd nanoparticle modified hydrogen production photocatalytic material, specifically comprising:
[0032] S1: Dissolve 0.405 g of 2-aminoterephthalic acid in 20 mL of N,N-dimethylformamide, then add 0.525 g of zirconium tetrachloride and 8.5 mL of acetic acid solution and fully dissolve;
[0033] S2: After heating at 100-140°C for 8-16 hours, cooling, centrifugal washing and drying to obtain UiO-66-NH2 powder;
[0034] S3: Grind 5g of thioacetamide into powder, dissolve in water, stir and dissolve, add Ce(NO3)3 solution to the thioacetamide solution to form a suspension with a molar ratio of Ce:S element of 2:3, and add 0.052g of UiO-66-NH2 material, dry and hydrothermally react to obtain Ce2S3 / UiO-66-NH2 material;
[0035] S4: 0.3 g of Ce2S3 / UiO-66-NH2 material and 0.15 g of NaBH4 were mixed and ground, heated at 300-400 °C under vacuum conditions for 0.5-1.5 h, cooled, washed, and dried to obtain Ce2S3 / UiO-66-NH2 material containing oxygen vacancies;
[0036] S5: Take 7 mL of 36% HCl solution, dilute it into 70 mL of distilled water, take 0.0178 g of PdCl2 powder and add it to the diluted HCl solution to obtain PdCl2 HCl solution;
[0037] S6: Add Ce2S3 / UiO-66-NH2 material containing oxygen vacancies into 120 ml of distilled water to dissolve, add 30 mL of methanol solution and PdCl2 HCl solution, mix well, irradiate with 300 W xenon lamp light source for 30 min, centrifuge, wash and dry to obtain Pd nanoparticle modified Ce2S3 / UiO-66-NH2 composite material, marked as 0.20-PSCUiO.
[0038] Example 2
[0039] Different from Example 1, the amount of UiO-66-NH2 material added in S3 is 0.139 g, the amount of Ce2S3 / UiO-66-NH2 material added in S4 is 0.4 g, the amount of NaBH4 added is 0.2 g, and the obtained Ce2S3 / UiO-66-NH2 composite material is marked as 0.40-PSCUiO.
[0040] Example 3
[0041] Different from Example 2, the amount of UiO-66-NH2 material added to S3 is 0.313 g, and the prepared Ce2S3 / UiO-66-NH2 composite material is marked as 0.60-PSCUiO.
[0042] Example 4
[0043] Different from Example 2, the amount of UiO-66-NH2 material added to S3 is 0.835 g, and the prepared Ce2S3 / UiO-66-NH2 composite material is marked as 0.80-PSCUiO.
[0044] Comparative Example 1
[0045] Different from Example 1, the amount of UiO-66-NH2 material added in S3 is 0 g, and Ce2S3 is directly obtained from S2.
[0046] Comparative Example 2
[0047] Different from Example 1, UiO-66-NH2 powder was prepared using only S1-S2.
[0048] Test Case
[0049] (1) Add 25 mg of Pd nanoparticle-modified Ce2S3 / UiO-66-NH2 material into 50 mL of 10% methanol solution and disperse by ultrasonic for 5 min;
[0050] (2) Transfer the completely ultrasonically dissolved mixed solution to a 100 mL reactor. Irradiate the top of the reactor with a xenon lamp. When installing the equipment, use vacuum grease, rubber rings and other materials to ensure the airtightness of the experimental equipment and to ensure that the experimental equipment does not leak. At the same time, use a flange to seal the high-transmittance quartz glass on the top of the reactor with the reactor.
[0051] (3) Connect the reactor to an all-glass automatic online trace gas analysis system (Labsolar-6A) and introduce circulating cooling water to keep the reactor system temperature at around 5°C;
[0052] (4) The mixed solution was stirred in the reactor for 30 min. At the same time, the reaction system and Labsolar-6A were evacuated by a vacuum pump to remove the air mixed in the entire system.
[0053] (5) After irradiating the material with a 300 W xenon lamp light source for 180 min, the process of photocatalytic decomposition of water to produce hydrogen was carried out. At the same time, the H2 produced by the system was sampled and measured every 30 min using Labsolar-6A, and the volume of H2 produced was tested using the equipped gas chromatograph.
[0054] like Figure 2 As shown in the figure, compared with pure Ce2S3 and UiO-66-NH2, the hydrogen production rate of Pd nanoparticle-modified Ce2S3 / UiO-66-NH2 composite material is significantly improved, and the hydrogen production rate of 0.60-PSCUiO composite is the highest, reaching 217.62μmol / h / g. This shows that the introduction of Pd nanoparticles on the surface of the material by photodeposition after Ce2S3 and UiO-66-NH2 are combined can improve the hydrogen production activity of the catalyst. Because the heterogeneous structure formed by the composite of Ce2S3 and UiO-66-NH2 can promote the separation of photogenerated electron-hole pairs, reduce the carrier recombination rate, and improve the hydrogen production activity of the catalyst.
[0055] First, the light absorption capacity of the catalyst will directly affect the utilization of light energy by the catalyst material, thereby affecting its hydrogen production rate. This patent characterizes the light absorption capacity through ultraviolet-visible diffuse reflectance spectroscopy, such as Figure 1 As shown in the figure, UiO-66-NH2 and Ce2S3 have strong ultraviolet absorption peaks between 200-350 nm, and the light absorption capacity of UiO-66-NH2 is better than that of Ce2S3. However, the absorbance of both in the visible light region shows a downward trend, indicating that the visible light absorption capacity of both is weak. Compared with pure UiO-66-NH2 and Ce2S3 materials, Pd nanoparticles modified Ce2S3 / UiO-66-NH2 composites still have good light absorption capacity in the ultraviolet region, and the visible light absorption capacity is significantly improved. This is mainly because the introduction of oxygen vacancies causes the color of the composite to deepen, and the plasma resonance effect of Pd nanoparticles on the surface of the composite material enhances the composite material's absorption capacity for visible light. The strong light absorption capacity of the composite material is conducive to improving its photocatalytic hydrogen production efficiency.
[0056] Secondly, the microscopic morphology of the catalyst material will affect the distribution and number of active sites of the catalyst material, thereby affecting the catalyst activity.
[0057] like Figure 3 As shown in the figure, the UiO-66-NH2 material is composed of stacked regular octahedral particles of different sizes. The surface of the octahedral crystal is relatively smooth, which is conducive to the rapid transmission of electrons on its surface and the separation of photogenerated carriers. The UiO-66-NH2 octahedral particles are stacked on each other, so that the material as a whole has many multi-level pore structures, which increases the specific surface area of the material and enables it to provide more adsorption sites, which is beneficial to improving the efficiency of photocatalytic hydrogen production.
[0058] like Figure 4As shown in the figure, the microscopic morphology of Ce2S3 material presents a fluffy and porous honeycomb structure with numerous pore structures inside. A large number of pore structures significantly increase the specific surface area of Ce2S3, which is beneficial to improving its photocatalytic hydrogen production activity. In addition, it can be observed that there are rough, uneven fine particles distributed on the surface of Ce2S3 material, which can make it easier for photogenerated charges to stay on the catalyst surface, which is beneficial to the transfer and capture of photogenerated electrons, making it easier to produce hydrogen through reduction reaction on the surface, further improving the hydrogen production activity of the catalyst.
[0059] like Figure 5 As shown, the scanning electron microscope image of Pd nanoparticle modified Ce2S3 / UiO-66-NH2 photocatalytic material shows that the composite material is a loose and porous sponge-like structure with a large number of loose pore structures on the surface, which increases the specific surface area of the material, enables it to provide more surface active sites, facilitates the transfer and capture of electrons, and enhances its photocatalytic hydrogen production efficiency.
[0060] In addition, if Figure 6 As shown in the element distribution spectrum of the composite material, the main elements Ce and S of Ce2S3, the main elements N and Zr of UiO-66-NH2, and the introduced metal element Pd can be clearly observed. The characterization results confirmed the successful preparation of Pd nanoparticle-modified Ce2S3 / UiO-66-NH2 photocatalytic materials. The uniformly mixed semiconductor material Ce2S3 and MOFs material UiO-66-NH2 in the composite material can form a closely contacted heterogeneous structure, which is beneficial to promote the directional migration of photogenerated charges, reduce the recombination rate of photogenerated charges, and improve the photocatalytic hydrogen production activity of the catalytic material.
[0061] However, the surface and interface structure of the catalyst material will affect the combination of different monomer materials and the formation of heterogeneous structures, thereby affecting the photocatalytic hydrogen production activity of the catalyst material. Figure 7 As shown in the figure, in the Pd nanoparticle modified Ce2S3 / UiO-66-NH2 material, it can be clearly observed that the octahedral UiO-66-NH2 is coated by the Ce2S3 material, and the UiO-66-NH2 and Ce2S3 are in close contact and have more contact interfaces, which is conducive to the formation of the Ce2S3 / UiO-66-NH2 heterostructure. The heterostructure can promote the separation of photogenerated electron-hole pairs and improve the hydrogen production efficiency of the catalyst.
[0062] The above embodiments are only used to illustrate the technical method of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical method of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical method of the present invention.
Claims
1. A preparation of a Pd nanoparticle modified hydrogen production photocatalytic material, characterized in that: Its preparation method is: S1: Grind thioacetamide into powder, dissolve in water, stir and dissolve, add Ce(NO3)3 solution to the thioacetamide solution, the amount of cerium nitrate solution added is such that the molar ratio of Ce:S elements in the solution is 2:3, and add UiO-66-NH2 material, dry and hydrothermally react to obtain Ce2S3 / UiO-66-NH2 material; S2: Ce2S3 / UiO-66-NH2 material and NaBH4 were mixed and ground, heated at 300-400°C under vacuum conditions for 0.5-1.5h, cooled, washed and dried to obtain Ce2S3 / UiO-66-NH2 material containing oxygen vacancies; S3: Ce2S3 / UiO-66-NH2 material containing oxygen vacancies was added into distilled water to dissolve, methanol solution and PdCl2 HCl solution were added, mixed evenly, irradiated with 300 W xenon lamp light source for 30 min, centrifuged, washed and dried to obtain highly dispersed Pd nanoparticles modified Ce2S3 / UiO-66-NH2 composite material; The ratio of thioacetamide, water and UiO-66-NH2 material is 5g:50mL:0.052-0.835g, the mass ratio of Ce2S3 / UiO-66-NH2 material and NaBH4 is 2:1, and the addition amount of Ce2S3 / UiO-66-NH2 material containing oxygen vacancies, distilled water and HCl solution containing PdCl2 is: 0.4g:160mL:77mL; The preparation method of the HCl solution containing PdCl2 is as follows: taking a 36% HCl solution, diluting it into distilled water, adding PdCl2 powder into the diluted HCl solution to obtain the HCl solution containing PdCl2, wherein the added amounts of the 36% HCl solution, distilled water and PdCl2 are 7 mL: 70 mL: 0.01 mol.
2. The preparation of the Pd nanoparticle modified hydrogen production photocatalytic material according to claim 1, characterized in that: The preparation method of the UiO-66-NH2 material is: (1) 2-aminoterephthalic acid is dissolved in N,N-dimethylformamide, and zirconium tetrachloride and acetic acid solution are added and fully dissolved; (2) After heating at 100-140°C for 8-16 hours, the mixture is cooled, centrifuged, washed and dried to obtain UiO-66-NH2 powder.
3. The preparation of the Pd nanoparticle modified hydrogen production photocatalytic material according to claim 2, characterized in that: The added amounts of the 2-aminoterephthalic acid, N,N-dimethylformamide, zirconium tetrachloride and acetic acid solution are 0.405 g: 20 mL: 0.525 g: 8.5 mL.
4. The use of the photocatalytic material prepared by the Pd nanoparticle-modified hydrogen-producing photocatalytic material according to claim 1, characterized in that: Application of Pd nanoparticles modified hydrogen-producing photocatalytic materials in photocatalytic hydrogen production technology.
Citation Information
Patent Citations
Ternary compound photocatalyst and preparation and application methods thereof
CN110252410A
Preparation method of flower-like molybdenum disulfide and UiO-66 combined photocatalyst
CN110918126A